Enhancing Design for Aesthetics Based on Product Platform Architecture - Abdullah, Ahmad Baharuddin; Mohd Ripin, Zaidi (Universiti Putra Malaysia Press, 2005)
Traditionally, most people buy a product based on performance and cost, but recently appearances, comfort and aesthetic are preferred. Customers are now becoming more complex and require not only good product performance but also appearance. To enhance product appearance, product platform has been proposed as new approach to the design for aesthetics. In this work, a platform is identified based on component sharing among the product variants. Then the aesthetic rules are applied to the platform. A Product Family Aesthetic Index (PFAI) was developed to measure the product performance. The evaluation is based on component commonality and aesthetic aspect. The result indicates that the Product Family Aesthetic Index had increased through redesigning several components in the product. A case study of the fan family was conducted to verify the methodology.